DINAMIKA PENDIDIKAN KARAKTER DALAM MEMBENTUK SISWA BERAKHLAKUL KARIMAH DI SMPN 1 BUAY BAHUGA LAMPUNG - Inka Fitri, Nanda; Selvi Aulia, Naila; Yuberti, Yuberti; Triolin Saputra, Rikky; Rahman Hamid, Abd; Baharudin, Baharudin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to explore the dynamics of character education implementation in shaping students with noble character (akhlakul karimah) at SMP Negeri 1 Buay Bahuga, Lampung using a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and document analysis, and were then thematically analyzed. The findings reveal that character education is implemented through habituation, teacher exemplification, and the reinforcement of religious culture in daily activities such as Quran recitation, congregational prayers, and religious extracurricular programs. The core values developed include religiosity, discipline, responsibility, empathy, tolerance, honesty, and integrity. The successful internalization of these values is strongly influenced by the synergy between teachers, the school, and the surrounding community. The implications of these findings highlight the importance of a collaborative and contextual approach in creating an effective character education ecosystem. The novelty of this research lies in its examination of how values of akhlakul karimah are not only taught but also brought to life through real practices, school culture, and socially embedded interactions within the local school context